Pengaruh Akses Modal, Kualitas SDM dan Peran Keluarga Terhadap Perkembangan Usaha Pedagang Perempuan di Pasar Tradisional - Ariyanti, Yulekhah (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
ABSTRACT In developing countries, women is strongly related with poor and marginalized people. Generally, small business women are independent business and related with family business. This study focused on women business, particulary traditional market traders as informal business. The development of this business will increase the family welfare. Considering the importance of the development effort of traditional market women, the purpose of writing this article is to investigate and analyze the effect of access to capital, quality of human resources, and the role of the family on the development of women’s enterprises in the traditional market that have a unique role as well as important influence to the family welfare. Key words: capital access, Human resource quality, family, business development, women entreprise.